A cold legacy a Madman's daughter novel - Shepherd, Megan (Balzer + Bray, 2015)
After escaping to a remote estate on the Scottish moors, owned by the enigmatic Elizabeth von Stein, Juliet Moreau, the product of her father's animal-human experiments, uncovers the truth about the manor's long history of scientific experimentation...and her own intended role in it